The Albian–Cenomanian transition and Oceanic Anoxic Event 1d – an example from the Boreal Realm. Issue 1 (4th January 2017) - Bornemann, André; Erbacher, Jochen; Heldt, Matthias; Kollaske, Tina; Wilmsen, Markus; Lübke, Nathalie; Huck, Stefan; Vollmar, Nele M.; Wonik, Thomas
Abstract: The upper Albian to lower Cenomanian interval in the Hanover area (Germany) is characterized by a well‐developed lithological transition from upper Albian monotonous (marly) claystones of several hundred metres thickness, which become enriched in biosilica in the topmost Albian, to increasingly CaCO3 ‐rich marls and limestones in the lower and middle Cenomanian. This study presents a new 165 m thick composite record spanning the latest Albian to mid‐early Cenomanian ( ca 103·0 to 97·5 Ma) based on two core drillings at Anderten in the central Lower Saxony Basin (east of Hanover), which is a sub‐basin of the North German Basin. Due to the lack or delayed occurrences of Tethyan biostratigraphic markers for the late Albian and early Cenomanian in the Boreal Realm, the definition of the Albian–Cenomanian boundary, as based on the lowest occurrence of Thalmanninella globotruncanoides, is not applicable. In order to overcome this issue, an integrated biostratigraphic–chemostratigraphic approach has been employed. In addition to biostratigraphy (calcareous nannofossils, ostracods, planktonic foraminifera and inoceramids), the Anderten succession has been studied using sedimentary geochemistry (CaCO3, total organic carbon, δ 13 C and δ 18 O), γ‐ray logging and X‐ray fluorescence core scanning. This approach enabled successful correlation of the composite Anderten record to European reference sections in England, south‐east France and Italy, as well as to further low‐resolution records from the Lower Saxony Basin (Wunstorf and Konrad 101 core). This work has made it possible to identify the δ 13 Ccarb expression of: (i) the Oceanic Anoxic Event 1d; (ii) the Albian–Cenomanian boundary interval; and (iii) potentially the Lower Cenomanian Event(s). Chemostratigraphic age assignments are supported by biostratigraphic results. Calcareous nannofossils indicate an extended Upper Cretaceous 0 (UC0) zone (upper Albian) up to Upper Cretaceous 2 (UC2; upper lower Cenomanian), and the occurrence of the ostracod Physocythere steghausi supports an early Cenomanian age for most of the upper part of the composite record. Notably, influxes of the planktonic foraminifer Thalmanninella aff. reicheli have previously been described from this area and the first appearance of this taxon is usually used to define the base of the middle Cenomanian Substage. However, findings from the Anderten cores and elsewhere suggest that this taxon has an apparently earlier first appearance, questioning previous age assignments from the Boreal Realm solely based on planktonic foraminifera. Due to both moderately well‐preserved microfossils and high sedimentation rates, the drilled succession of Anderten is considered as a potential Boreal reference section for the Albian–Cenomanian transition.